Áurea Moretti a mulher, a resistência e a tortura: um estudo sobre a participação feminina contra a ditadura militar brasileira 1965-1975 - Russo, Pedro Fernandes [UNESP] (2015)
This research aims at understanding the role and the daily life of women during the resistance to the Brazilian military government (1964-1985). Therefore, it will be analyzed the life path of the former political prisoner and left-wing partisan Áurea Moretti Pires, who was one of the leaders of Forças Armadas de Libertação Nacional (FALN), a guerrilla group based in the Ribeirão Preto region - São Paulo state's interior - which was dismantled in 1969. With Vanderley Caixe, Mario Bugliani, Mario Lorenzato, and others, Áurea organized political demonstrations and the newspaper O Berro against the military government. As studies about the women's daily life in guerrilla are not well known, this research aims at analyzing, from Áurea's testimonies, how was her clandestine life; the difficulties during training and daily life among the guerrilla fighters; the physical and psychological tortures perpetrated by State operatives; the court case that sentenced her to prison for six years; as well as her experiences as political prisoner. This analysis covers the period from 1965 - when Áurea joined guerrilla - to 1975 - when she was released. However, in order to place the formation of Áurea's thought, her experiences before 1965 and after 1975 are also considered